Engineered Biofilm: Innovative Nextgen Strategy for Quality Enhancement of Fermented Foods - Ghosh, Sreejita; Nag, Moupriya; Lahiri, Dibyajit; Sarkar, Tanmay; Pati, Siddhartha; Kari, Zulhisyam Abdul; Nirmal, Nilesh P.; Edinur, Hisham Atan; Ray, Rina Rani (Frontiers in Nutrition, 2022)
Microbial communities within fermented food (beers, wines, distillates, meats, fishes, cheeses, breads) products remain within biofilm and are embedded in a complex extracellular polymeric matrix that provides favorable growth conditions to the indwelling species. Biofilm acts as the best ecological niche for the residing microbes by providing food ingredients that interact with the fermenting microorganisms' metabolites to boost their growth. This leads to the alterations in the biochemical and nutritional quality of the fermented food ingredients compared to the initial ingredients in terms of antioxidants, peptides, organoleptic and probiotic properties, and antimicrobial activity. Microbes within the biofilm have altered genetic expression that may lead to novel biochemical pathways influencing their chemical and organoleptic properties related to consumer acceptability. Although microbial biofilms have always been linked to pathogenicity owing to its enhanced antimicrobial resistance, biofilm could be favorable for the production of amino acids like l-proline and L-threonine by engineered bacteria. The unique characteristics of many traditional fermented foods are attributed by the biofilm formed by lactic acid bacteria and yeast and often, multispecies biofilm can be successfully used for repeated-batch fermentation. The present review will shed light on current research related to the role of biofilm in the fermentation process with special reference to the recent applications of NGS/WGS/omics for the improved biofilm forming ability of the genetically engineered and biotechnologically modified microorganisms to bring about the amelioration of the quality of fermented food.